The Effect Of Using Online Technology On Quality Of Services For Opening Accounts In BCA Bank Surabaya - Novaquita Novaquita (NAROTAMA UNIVERSITY, Indonesia, 2019)
This study aims to analyze the effect of perceived usefulness, perceived ease of use, convenience, and security have a simultaneous and partial effect on quality online technology usage services for customers in opening accounts at BCA Bank Surabaya .The method used by the author is a quantitative method with an approach analytical descriptive. The research variable used is TAM (Technology Acceptance Model). The research results show that Perceived Usefulness (X1), Perceived Ease of Use (X2), Comfort (X3), and Security (X4), affect simultaneously to dependent variable Service Quality (Y). Thus the first hypothesis is states